2014
DOI: 10.1186/bf03353314
|View full text |Cite
|
Sign up to set email alerts
|

P-T conditions of cataclastic deformation associated with underplating: An example from the Cretaceous Shimanto complex, Kii Peninsula, SW Japan

Abstract: P-T conditions of cataclastic deformation associated with underplating in subduction zone are estimated from fluid inclusions within the post-mélange veins in the Cretaceous Shimanto Belt, Kii Peninsula, SW Japan. Both cataclasite and post-mélange veins cut the mélange fabric and are distributed along the thrusts in duplex structure. The homogenization temperatures range from 200 (±10)• C to 270 (±42)• C corresponding to entrapment pressures over a wide range from 145 (±5) MPa to 304 (−20) MPa. Our results hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
2
25
0
2
Order By: Relevance
“…Geological studies of on-land tectonic mélange have shown that sandstones are finely broken [e.g., Cowan, 1982;Byrne, 1984;Agar, 1990]. Although the mechanical behavior of sandstone has been well studied by many experiments [e.g., Zhang et al, 1990aZhang et al, , 1990bMarone et al, 1990;Wong et al, 1997], quantitative evaluation of the deformation conditions are sparse, except for some inferences on the P-T conditions [Vrolijk, 1987;Hashimoto et al, 2002Hashimoto et al, , 2003Lewis and Byrne, 2003;Matsumura et al, 2003]. Constraining the deformation and lithification process of sandstone is therefore one of the keys to understanding the onset of the seismogenic zone.…”
Section: Introductionmentioning
confidence: 99%
“…Geological studies of on-land tectonic mélange have shown that sandstones are finely broken [e.g., Cowan, 1982;Byrne, 1984;Agar, 1990]. Although the mechanical behavior of sandstone has been well studied by many experiments [e.g., Zhang et al, 1990aZhang et al, , 1990bMarone et al, 1990;Wong et al, 1997], quantitative evaluation of the deformation conditions are sparse, except for some inferences on the P-T conditions [Vrolijk, 1987;Hashimoto et al, 2002Hashimoto et al, , 2003Lewis and Byrne, 2003;Matsumura et al, 2003]. Constraining the deformation and lithification process of sandstone is therefore one of the keys to understanding the onset of the seismogenic zone.…”
Section: Introductionmentioning
confidence: 99%
“…No systematic variation in homogenization temperatures from calcite hosts has been noted suggesting that the constant density assumption for the trapped fluids is valid (e.g., Roedder, 1984). (Hashimoto et al, 2002Matsumura et al, 2003;Hashimoto et al, 2012). Although the data are limited, the pressuretemperature condition for the Mugi mélange tends to shift to a higher thermal gradient, possibly because of the relatively young and hot plate subduction (Matsumura et al, 2003).…”
Section: Pressure-temperature Conditionsmentioning
confidence: 98%
“…Pressure-temperature conditions for the formations of the extension and the shear veins have been previously estimated on the basis of fluid inclusion analysis from three mélange zones in the Cretaceous Shimanto Belt: the Mugi mélange (Matsumura et al, 2003), the Miyama formation (Hashimoto et al, 2002, and the Yokonami mélange (Hashimoto et al, 2012) (see locations in Figure 1). For the Yokonami mélange, the pressure-temperature condition only for the shear veins was obtained.…”
Section: Pressure-temperature Conditionsmentioning
confidence: 99%
See 2 more Smart Citations